The influence of Fusarium ear infection on the maize yield and mycotoxin content (Transylvania-Romania). - Nagy, E.; Haş, V.; Haş, I.; Suciu, A.; Florian, V. (Plant Breeding and Seed Science, 2011)
Maize is the host for a large number of pathogens, which invade all of its organs from the germination until being harvest, ear and grain infection often persistent even during storage. Diseases, through their symptoms reduce significantly the quantity and the quality of yield, estimated between 7-17% but, in the favorable years for this disease, they can be much greater. Fusarium diseases reduce yield value and quality by massive accumulation of Fusarium mycelium biomass (about 85%) on grain and ears and by mycotoxin contamination such as deoxynivalenol (DON), zearalenone (ZEA) and fumonisins (FUM). In this paper are presented aspects regarding the reaction of some maize hybrids under Fusarium spp. natural and artificial infections; the effect of Fusarium ear infection on yield, grain chemical composition, and mycotoxin content; the correlation between ear rot disease degree and yield ability, starch, protein and fat content. ANOVA evidenced the significant influence of experimental factors: infection conditions with Fusarium spp., maize genotypes, and their interaction on expression of the disease degree, yield capacity, protein, starch, fat and DON content. Average yield losses ranged between 7,0-9,3% during the experimental period. The hybrids Turda Star and Turda Favorit were more resistant to Fusarium ear rot, and Turda 165 was the most susceptible one. The artificial infection of ear with Fusarium spp. determined significantly decrease of starch and fat content and increases the protein and DON content for the most part of maize hybrids. Between rot diseased kernels and DON content a positive correlation was determined.